2016
DOI: 10.1111/1756-185x.12834
|View full text |Cite
|
Sign up to set email alerts
|

Association between clinical and sonographic synovitis in patients with painful knee osteoarthritis

Abstract: This study revealed a positive correlation between ultrasonographic synovitis and total WOMAC score, WOMAC pain and physical function sub-score. There was no association between sonographic signs of arthritis and WOMAC joint stiffness sub-score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The questionnaire we used is a useful tool to diagnose OA, including in the very early stages, and it also helps determine the severity of synovitis, which is an important finding in knee OA. 19,26,27 Thanks to this questionnaire, we believe we were able to obtain a reasonable assessment of the extent of OA in each participant, including those in the very early stages and those who would not have shown changes on radiographic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire we used is a useful tool to diagnose OA, including in the very early stages, and it also helps determine the severity of synovitis, which is an important finding in knee OA. 19,26,27 Thanks to this questionnaire, we believe we were able to obtain a reasonable assessment of the extent of OA in each participant, including those in the very early stages and those who would not have shown changes on radiographic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…More than 2 years before onset, patients with AKOA present with more pain, synovitis-effusion of larger volumes and signal alterations in the infrapatellar fat pad (IFP) compared with patients who develop typical knee OA 17,18 . MRI and ultrasonography have also been used to evaluate associations between synovitis and pain 5,[19][20][21][22][23][24][25][26][27] , finding that synovitis contributes to pain in OA. Of note, a study found that synovitis partially mediates the association between cartilage damage loss and worsening pain: each 0.1-mm loss of cartilage over 24 months translated to an increase in the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain subscale score of 0.32 (95% CI 0.21-0.44) 28 .…”
mentioning
confidence: 99%
“…In patients with OA, synovial tissue affected by fibrosis becomes thicker and rigid [30]. These symptoms contribute to the main characteristics of OA, such as joint pain and stiffness [57]. Fibrosis results in fibrin deposition in the synovial tissue [58].…”
Section: Synovial Fibrosis In Oamentioning
confidence: 99%